Recent Advances Regarding Precious Metal-Based Electrocatalysts for Acidic Water Splitting - Yuanting Peng; Yucong Liao; Donghao Ye; Zihan Meng; Rui Wang; Shengqiu Zhao; Tian Tian; Haolin Tang (Nanomaterials, 2022)
Electrochemical water splitting has wide applicability in preparing high-density green energy. The Proton exchange membrane (PEM) water electrolysis system is a promising technique for the generation of hydrogen due to its high electrolytic efficiency, safety and reliability, compactness, and quick response to renewable energy sources. However, the instability of catalysts for electrochemical water splitting under operating conditions limits their practical applications. Until now, only precious metal-based materials have met the requirements for rigorous long-term stability and high catalytic activity under acid conditions. In this review, the recent progress made in this regard is presented and analyzed to clarify the role of precious metals in the promotion of the electrolytic decomposition of water. Reducing precious metal loading, enhancing catalytic activity, and improving catalytic lifetime are crucial directions for developing a new generation of PEM water electrolysis catalysts. A summary of the synthesis of high-performance catalysts based on precious metals and an analysis of the factors affecting catalytic performance were derived from a recent investigation. Finally, we present the remaining challenges and future perspectives as guidelines for practical use.